Slippery liquid-infused porous surfaces showing marine antibiofouling properties - Xiao, Linlin; Grunze, Michael (ACS applied materials & interfaces, 2013)
Marine biofouling is a longstanding problem because of the constant challenges placed by various fouling species and increasingly restricted environmental regulations for antifouling coatings. Novel nonbiocidal strategies to control biofouling will necessitate a multifunctional approach to coating design. Here we show that slippery liquid-infused porous surfaces (SLIPSs) provide another possible strategy to obtaining promising antifouling coatings. Microporous butyl methacrylate-ethylene dimethacrylate (BMA-EDMA) surfaces are prepared via UV-initiated free-radical polymerization. Subsequent infusion of fluorocarbon lubricants (Krytox103, Krytox100, and Fluorinert FC-70) into the porous microtexture results in liquid-repellent slippery surfaces. To study the interaction with marine fouling organisms, settlement of zoospores of the alga Ulva linza and cypris larvae of the barnacle Balanus amphitrite is tested in laboratory assays. BMA-EDMA surfaces infused with Krytox103 and Krytox100 exhibit remarkable inhibition of settlement (attachment) of both spores and cyprids to a level comparable to that of a poly(ethylene glycol) (PEG)-terminated self-assembled monolayer. In addition, the adhesion strength of sporelings (young plants) of U. linza is reduced for BMA-EDMA surfaces infused with Krytox103 and Krytox100 compared to pristine (noninfused) BMA-EDMA and BMA-EDMA infused with Fluorinert FC-70. Immersion tests suggest a correlation between the stability of slippery coatings in artificial seawater and fouling resistance efficacy. The results indicate great potential for the application of this concept in fouling-resistant marine coatings.